IMPLEMENTASI ASESMEN DIAGNOSTIK SEBAGAI DASAR PELAKSANAAN PEMBELAJARAN DI SEKOLAH DASAR - Husnul Khatimah; Muhammad Sofwan; Hendra Budiono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The importance of diagnostic assessment as a basis for designing adaptive learning in elementary schools. Although the Independent Curriculum emphasizes diagnostic assessment, its implementation in the field still faces obstacles, particularly related to teacher understanding, instrument development, and implementation of non-cognitive assessments. This study aims to describe the implementation of diagnostic assessment as a basis for learning implementation at SD Negeri 55/I Sridadi. The study used a qualitative approach with a case study method. Data were obtained through observation, interviews, and document studies, then analyzed using the Miles and Huberman model through the stages of data reduction, data presentation, and conclusion drawing. Data validity was tested using triangulation of sources, techniques, and time. The results showed that teachers had routinely implemented non-cognitive diagnostic assessments at the beginning of the lesson and throughout the learning process through behavioral observations, simple questionnaires, and interviews. The assessment results were used to map students' motivations, interests, attitudes, and learning barriers, which became the basis for adjusting learning strategies, student grouping, and providing mentoring. Obstacles encountered included limited time, teachers' ability to develop instruments, and administrative burdens. This study confirms that diagnostic assessment plays a strategic role in realizing more personalized, inclusive, and effective learning in elementary schools